The significance of supply chain management with regard to the attainment of value and strategic objectives for municipalities within South Africa : a case study - Bent, Reginald Anthony (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPA)--Stellenbosch University, 2014.